Detection of Uropathogens by Using Chromogenic Media (Hicrome UTI agar), CLED agar and other Conventional Media (Faridpur Medical College Journal, 2011)
This study was undertaken to find media better than routinely used media in isolation of uropathogens.Three hundred urine samples having pus cells >_ 5/ HPF were enrolled for the study. Comparison of isolation and identification of uropathogens among HiCrome UTI Agar media, 5% Sheep Blood agar & MacConkey agar and CLED agar media were done. Among them 95(31.67%) samples showed single growth, 6 (2%) showed mixed growth and 199 (66.67%) showed no growth. Rate of presumptive identification of organisms in primary culture plate were high in HiCrome UTI agar media. For Escherichia coli, it was 94.20% whereas in CLED agar it was 79.71% and by Blood agar and MacConkey agar media in combination it was 82.61%. All the Enterococcus spp. were identified in HiCrome UTI agar media, 33.33% in CLED agar media but none in Blood agar and MacConkey agar media. Among the mixed growth, 100% organisms were identified on HiCrome UTI Agar media due to distinct colour produced by the different organisms, whereas in one (16.67%) sample (mixed Esch.coli and Pseudomonas spp.) organisms were identified on other three media. Key words: UTI; Uropathogen; HiCrome UTI Agar media DOI: 10.3329/fmcj.v6i1.7411 Faridpur Med. Coll. J. 2011;6(1): 46-50